How Political and Social Trust Can Impact Social Distancing Practices During COVID-19 in Unexpected Ways - Woelfert, Frederike S.; Kunst, Jonas R. (Frontiers in Psychology, 2020)
In times of the coronavirus, complying with public health policies is essential to save lives. Understanding the factors that influence compliance with social distancing measures is therefore an urgent issue. The present research investigated the role of political and social trust for social distancing using a variety of methods. In Study 1 (N = 301), conducted with a sample from the United Kingdom in the midst of the virus outbreak (i.e., the first wave), neither political nor social trust had main associations with self-reported social distancing tendencies. However, both factors interacted such that social trust was associated with lower social distancing tendencies among participants with low levels of political trust. In Study 2, using an experimental longitudinal design and again conducted with a sample collected from the United Kingdom (N = 268) during the first wave of the pandemic, social distancing practices increased over time, independent of an experimental manipulation of political trust. Moreover, while the interaction between political and social trust from the first study could not be conceptually replicated, social trust was positively related to social distancing intentions. Moving from the individual to the country level and assessing actual behavior at both the first and second wave of the pandemic, in Study 3 (N = 65 countries), country-level political trust was related to less social distancing during the first wave. Social trust was related to a higher growth rate of infections. Against the background of these inconsistent findings, we discuss the potential positive and unexpected negative effects of social trust for social distancing.